Origin of the π-π spacing change upon doping of semiconducting polymers - Liu, Wenlan; Müller, Lars; Ma, Shuangying; Barlow, Stephen; Marder, Seth R.; Kowalsky, Wolfgang; Köhn, Andreas; Lovrincic, Robert (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
Although there is an agreement about the local structural order of semiconducting polymers such as poly(3-hexylthiophene) (P3HT), there is still a debate over the impact of molecular doping. One prevalent interpretation is that dopant molecules intercalate in the π-π stacking of crystallites; however, this idea has recently been challenged. We present here electron diffraction measurements of P3HT doped with the two dopants 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) and molybdenum tris[1-(methoxycarbonyl)-2-(trifluoromethyl)-ethane-1,2-dithiolene] (Mo(tfd-CO2Me)3), which have considerably different sizes and shapes, processed by different doping techniques. We observe a reduction in the π-π spacing of P3HT upon doping with both dopant molecules and doping techniques. These data are not consistent with both of the dopants intercalating in the π-π stacks and an alternative explanation is, therefore, required to explain these results. Density functional theory calculations for P3HT model oligomers suggest that the polaron delocalizes between adjacent chains and thus leads to attractive forces that reduce the π-π spacing, without the physical presence of any dopant molecules. Our study emphasizes that not only geometric effects induced by dopant molecules lead to the observed reduction of π-π spacing, but the charging itself.
Gesehen am 05.03.2020